Analisis Proteksi Radiasi Ruang Terkontrol Cath-Lab Selama Tindakan Pemeriksaan Di RSUD Murjani Sampit - Manik, Jhon Wesly; Hakim, Luqman (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Continuous exposure to radiation on Cah Lab equipment during procedures can produce significant environmental radiation. Therefore, the safety of medical worked and the public is very important and must comply with PERKA BAPETEN No. 4 of 2020 which sets a radiation exposure limit of 20 mSv/year for radiation workers and 1 mSv/year for the environment or community. This research focused on measuring radiation exposure at three different points in the Cath Lab control room, namely point 1 on the operator's glass, point 2 on the top door, and point 3 on the bottom door. The measurement method uses a Gamma Surveymeter which is placed at a distance of 30 cm from each measurement point, then the radiation background value is recorded and each measurement point is carried out 30 times during exposure during the inspection, with variations in kV and mA. The measurement results show that the radiation exposure value at point 1 (glass) is 0.183 mSv/year, point 2 (the upper door which is parallel to the organ area) is 0.045 mSv/year, and point 3 (the bottom door which is parallel to the organ area reproduction) is 0.102 mSv/yr. All these measurement results are still within the safe limits set in accordance with PERKA BAPETEN No.4 of 2020.